The change of psychosocial stress factors in families with infants and toddlers during the COVID-19 pandemic. A longitudinal perspective on the CoronabaBY study from Germany - Buechel, Catherine; Friedmann, Anna; Eber, Stefan; Behrends, Uta; Mall, Volker; Nehring, Ina (Frontiers in Pediatrics, 2024)
Background Over nearly three years, the COVID-19 pandemic has had a lasting impact on people's lives and mental health worldwide with its far-reaching restrictions and concerns about infections and other personal consequences. Families were particularly affected and showed increased stress and psychological problems. Long-term effects cannot be ruled out. So far, data on young families are sparse. The present longitudinal analysis (n = 932) of the CoronabaBY study investigated the development of parenting stress, parental affective symptoms, and child's mental health in young families with children aged 0–3 years in Germany as well as potential influencing factors. Methods The observational study includes two measurement points over the course of the pandemic (baseline and follow-up). Data was collected by app using standardized questionnaires. Results N = 932 participants, mainly mothers (94.7%) born in Germany (93.1%) with higher education (61.3% with at least high school diploma) and a comfortable financial situation participated in the longitudinal study. Children were on average 14.7 months old at baseline (SD: 12, range: 1–39 months). While the proportion of parents who perceived the pandemic as stressful decreased significantly from baseline (60%) to follow-up (52.3%), the proportion with parenting stress increased significantly (from 40.1% to 45.4%). Both parental and child mental health problems remained constant over time, with infants crying/feeding/sleeping problems ranging above pre-pandemic comparative data. Most predictive for high parenting stress at follow-up was high parenting stress at baseline. This was also true for parental affective symptoms (depression/anxiety) and child mental health problems. Conclusions Despite faded pandemic restrictions, parents remained burdened. Support services do not appear to have been sufficient to help families out of their stressful situation. Our results indicate a need for action regarding low-threshold services that effectively reach affected families. Trial registration The study was pre-registered in OSF (https://osf.io/search/?q=tksh5&page=1).